2019
DOI: 10.1177/0263617419868076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pore structure characteristics and adsorption characteristics of coals with different destruction types

Abstract: The occurrence of coal and gas outbursts is closely linked to the presence of tectonic coal. To study the pore structure characteristics and adsorption characteristics of different destruction types of coal, nondestructive coal, destructive coal, strongly destructive coal, pulverized coal, and fully pulverized coal are selected based on the coal and gas outburst mine identification specifications. The experimental methods used are liquid nitrogen adsorption, mercury intrusion porosimetry and CH 4 isothermal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
2
30
0
2
Order By: Relevance
“…In particular, the adsorption capacity of coalbed methane (CBM) is closely related to the pore development degree and pore structure characteristics. Therefore, the research on the pore structure characteristics of coal is meaningful for gas disaster prevention and CBM extraction and utilization [8][9][10]. As specified by the Hodot decimal classification standard [11][12][13], the pores in coal can be divided into five categories according to the pore size, i.e., micropores (<10 nm), small pores (10-100 nm), mesopores (100-1,000 nm), macropores (>10,000 nm), and visible pores (>100,000 nm).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the adsorption capacity of coalbed methane (CBM) is closely related to the pore development degree and pore structure characteristics. Therefore, the research on the pore structure characteristics of coal is meaningful for gas disaster prevention and CBM extraction and utilization [8][9][10]. As specified by the Hodot decimal classification standard [11][12][13], the pores in coal can be divided into five categories according to the pore size, i.e., micropores (<10 nm), small pores (10-100 nm), mesopores (100-1,000 nm), macropores (>10,000 nm), and visible pores (>100,000 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Coal and gas outburst is a complex dynamic phenomenon associated with coal, rock, and gas in coal mines, which is one of the most serious natural disasters in the process of coal mining (Li et al, 2017;C. Wang et al, 2017;Yue et al, 2019aYue et al, , 2019b. Coalbed methane is considered a driving force of coal and gas outbursts.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Field tests have shown that the gas emission from coal increases during the water injection process 18,[21][22][23] ; in contrast, experimental results have shown that an increase in the moisture content of coal has a significant inhibitory desorption effect on the adsorbed gas. 24,25 Thus, it is necessary to determine the influence of external water on the desorption character of the adsorbed coalbed methane in coal.…”
Section: Introductionmentioning
confidence: 99%
“…As the permeability is often very low for complex coal structures, hydraulic methods that enable an increase in the water content and thus reduce the gas pressure of coal seams, including coal seam water injection, 17 hydraulic punching, and hydraulic extrusion, are the main techniques used to improve permeability before coal mining 18‐20 . Field tests have shown that the gas emission from coal increases during the water injection process 18,21‐23 ; in contrast, experimental results have shown that an increase in the moisture content of coal has a significant inhibitory desorption effect on the adsorbed gas 24,25 . Thus, it is necessary to determine the influence of external water on the desorption character of the adsorbed coalbed methane in coal.…”
Section: Introductionmentioning
confidence: 99%